2010
DOI: 10.2174/187152410793429700
|View full text |Cite
|
Sign up to set email alerts
|

Ectodomain Shedding and Regulated Intracellular Proteolysis in the Central Nervous System

Abstract: The term Ectodomain Shedding (ES) refers to extracellular domain proteolytic release from cell membrane molecules. This proteolysis is mediated mainly by matrix metalloproteases (MMP) or disintegrin and metalloproteases (ADAM), although some other proteases may mediate it. Virtually, all functional categories of cell membrane molecules are subject of this kind of proteolysis, for this reason ES is involved in different cellular processes such as proliferation, apoptosis, migration, differentiation or pathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 91 publications
(212 reference statements)
0
16
0
Order By: Relevance
“…Transmembrane proteins, such as CX3CL1, can be proteolytically cleaved at the juxtamembrane region, which results in the detachment of their extracellular region (ectodomain) in a process known as ectodomain shedding [18]. This shedding process can release proteins such as cytokines and growth factors from their membrane-bound form, or alternatively, it can down-regulate receptors from the cell surface [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transmembrane proteins, such as CX3CL1, can be proteolytically cleaved at the juxtamembrane region, which results in the detachment of their extracellular region (ectodomain) in a process known as ectodomain shedding [18]. This shedding process can release proteins such as cytokines and growth factors from their membrane-bound form, or alternatively, it can down-regulate receptors from the cell surface [18].…”
Section: Introductionmentioning
confidence: 99%
“…This shedding process can release proteins such as cytokines and growth factors from their membrane-bound form, or alternatively, it can down-regulate receptors from the cell surface [18]. Proteases such as the matrix metalloprotease (MMP) family shed several cell surface substrates [19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…any transmembrane proteins on the cell surface are subject to proteolytic cleavage of their ectodomains, predominantly by metalloproteases (ectodomain shedding) (1)(2)(3). Ectodomain shedding regulates numerous important molecules involved in signal transfer between the extracellular space and the cell's interior and thus influences many cellular functions (1,3).…”
mentioning
confidence: 99%
“…Ectodomain shedding regulates numerous important molecules involved in signal transfer between the extracellular space and the cell's interior and thus influences many cellular functions (1,3). This includes, for example, the biological availability of epidermal growth factor (EGF) receptor ligands such as neuregulin (NRG1) (4,5) and the modulation of complex cellular phenotypes required for contact inhibition of cells involving the hyaluronic acid receptor CD44 (4).…”
mentioning
confidence: 99%
“…Interestingly, it has been reported that NMDAR has been found to associate with metabotropic dopamine receptors [149]. There is also a possibility that Ca 2+ flux-independent metabotropic-like NMDAR function could be the result of proteolytic cleavage, as that already reported for NMDAR subunit GluN1 [150], that occurs to other membrane molecules [151]. In addition, GluN2C subunit-mediated IC signaling, found highly expressed in most transcriptome analysis of astrocytes, but that has been poorly studied, could be involved.…”
Section: Insights Regarding Astrocytic Nmdarmentioning
confidence: 83%